The challenges of sport psychology delivery in elite and professional sport: Reflections from experienced sport psychologists - McDougall, M.; Nesti, M.; Richardson, D. (The Sport Psychologist, 2015)
The challenges encountered by sport psychologists operating within elite and professional sports teams have arguably been inadequately considered (Nesti, 2010). It has been suggested that this may be due to the inaccessibility of elite team environments (Eubank, Nesti, & Cruickshank, 2014; Nesti, 2010). The purpose of this research was to examine the challenges facing practitioners who operate in elite environments and to illuminate how these were experienced. Qualitative interviews with six experienced applied sport psychologists were conducted and a narrative themed analysis undertaken. Four main themes emerged as most prevalent and meaningful: challenges to congruence, a broader role: managing multiple relationships, the influence of elite sport cultures, and surviving and thriving were presented in narrative form. Practitioners provided experiential insight into how specific challenges were understood and dealt with, and how they are able to provide an effective service while managing themselves and the demands of the environment.